2004
DOI: 10.1023/b:biop.0000041104.54922.31
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Drought Tolerance of Different Stylosanthes Accessions

Abstract: Twenty genotypes of Stylosanthes consisting four species were evaluated under rain fed condition employing biochemical and physiological attributes to select drought tolerant lines. Relative water content measured at 50 % flowering stage of the plants showed significant variations among the lines which ranged from 32.11 in S. scabra RRR94-86 to 83.33 % in S. seabrana 2539. The results indicated that S. scabra genotypes were more tolerant to drought over other lines as evidenced by high leaf thickness, proline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 13 publications
(11 reference statements)
0
16
0
Order By: Relevance
“…One way many plants coped with water stress is to synthesize and accumulate compounds termed osmoprotectants (or compatible solutes) including polyols, sugars, amino acids, betaines, etc (Bohnert and Jensen 1996). Generally, in many plants free proline accumulates in response to a wide range of stresses, such as salinity stress (Delauney and Verma 1993), drought stress (Zhang et al 1995, Chandra et al 2004, extreme temperatures , heavy metal toxicity ) and nutrient deficiency . However, the precise function of proline accumulation is still a controversial question (Hare et al 1999).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…One way many plants coped with water stress is to synthesize and accumulate compounds termed osmoprotectants (or compatible solutes) including polyols, sugars, amino acids, betaines, etc (Bohnert and Jensen 1996). Generally, in many plants free proline accumulates in response to a wide range of stresses, such as salinity stress (Delauney and Verma 1993), drought stress (Zhang et al 1995, Chandra et al 2004, extreme temperatures , heavy metal toxicity ) and nutrient deficiency . However, the precise function of proline accumulation is still a controversial question (Hare et al 1999).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…Higher LMA can be produced by increases in leaf density, in leaf thickness or both. High leaf thickness is often related to a great tolerance to drought (Chandra et al 2004), but recent studies showed an important decrease in leaf thickness under low irradiance and an important increase in leaf density under low soil water availability (Witkowsky and Lamont 1991, Groom andLamont 1997, Niinemets 2001). Therefore, it seems that sclerophyll leaf structure is not linked to any particular environmental stress and that can respond differently in sun than in the shade leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Proline and glycinebetaine are well known compatible osmolytes that accumulate in plants under osmotic stress (Hare and Cress 1997, McNeil et al 1999, Chandra et al 2004, Jimenez-Bremont et al 2006. Their biosynthetic pathways are also well known.…”
Section: Introductionmentioning
confidence: 99%